A Review: The Impact of Viral Mutations on theTtransmission Dynamics of the Monkeypox Virus - Naser Abbasa , Saly; Jassim Manshad , Maha; Maytham Oleiwi , Bassam (Pure Sciences International Journal of Kerbala, 2025)
Monkeypox virus (MPXV) is an emerging zoonotic pathogen under the Orthopoxvirus genus, primarily found in Central and West Africa. It shares similarities with the variola virus, responsible for smallpox, and causes symptoms such as fever, rash, and swollen lymph nodes. The virus spreads through direct contact with infected animals, people, or contaminated objects. The recent rise in monkeypox cases beyond its usual regions has raised global health concerns. Understanding its epidemiology, clinical symptoms, and transmission is crucial for effective prevention and control. Research on vaccines and treatments is essential to mitigate future outbreaks.Viral mutations play a significant role in the evolution and behavior of MPXV, affecting transmission, virulence, and immune system interactions. This review examines how genetic changes influence the virus’s spread, enhance its pathogenicity, and alter immune responses. Mutations in surface proteins may improve viral attachment to host cells, facilitating transmission. Additionally, changes in key viral genes can help evade immune detection, leading to more severe outcomes. These mutations pose public health challenges, potentially reducing vaccine and diagnostic effectiveness.Understanding the impact of viral mutations on monkeypox is crucial for effective surveillance, prevention, and treatment strategies. This analysis emphasizes the importance of continuous genomic monitoring to anticipate changes in monkeypox epidemiology and adapt public health responses accordin]gly.